The role of the private sector in the development of the economics and services of Hajj and Umrah - Hurubi, Ibrahim Ahamad (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aimed to reveal the role of the private sector in the development of the economics and services of Hajj and Umrah, and to achieve this goal the study relied on the analytical descriptive curriculum. The study tool was a questionnaire and interview form applied to a sample of 120 researchers. The findings of the study found the private sector's inability to lead its current possibilities and experiences, as evidenced by the low services and complaints of pilgrims and practitioners. and a significant increase in service prices with a clear decline in services after the private sector's entry into service delivery. The lack of proper and adequate oversight of the agencies operating in the Hajj and Umrah market resulted in the loss of the rights of contractors and pilgrims. The results recommended that a body should be established to bring together the public and private sectors to take over pilgrims' affairs and upgrade services.
Keywords: Private Sector; Umrah; Hajj; Services; Economics